ACADEMIC COMPETITIONS: PERCEPTIONS OF LEARNING BENEFITS FROM A SCIENCE BOWL COMPETITION - Robert Kuech; Robert Sanford (European Scientific Journal, ESJ, 2014)
The National Science Bowl® emphasizes a broad range of general and specific content knowledge in all areas of math and science. The achievements made through the science bowl experience are independent of the classroom environment and generally occur because the student has volunteered on his/her own to enter the competition and be part of the team. An important question to ask in light of the effort it takes to run regional or national science competitions is whether or not the event makes a difference to the student. And if it makes a difference, does it improve student learning or student attitudes about science. The data indicates that a statistically significant portion of the students competing in the Northern New England Regional Science Bowl Competition report that the event has a positive impact on the participants and fosters learning in science and mathematics. These data support findings that have been reported for other forms of academic competitions that are involved with science and mathematics.